2018
DOI: 10.1017/ice.2017.287
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Airway Management in a Simulation of Highly Contagious Isolated Patients: Both Isolation Strategy and Device Type Matter

Abstract: OBJECTIVE To compare 6 airway-management devices in 3 isolation scenarios regarding their effect on airway management: portable isolation unit (PIU), personal protective equipment (PPE), and standard protection measures METHODS In total, 30 anesthesiologists working in emergency medical services performed airway management on mannequins in 3 isolation settings using 6 different airway management devices (in random order): (1) standard Macintosh laryngoscope; (2) Airtraq SP-video-laryngoscope; (3) i-gel; (4) LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Plazikowski et al compared airway management in the Rega PIU with airway management under standard protective measures [7]. The study compared intubation of mannequins using a standard laryngoscope, a video laryngoscope, or cricothyrotomy.…”
Section: Setup and Our Experience With The Rega Piumentioning
confidence: 99%
“…Plazikowski et al compared airway management in the Rega PIU with airway management under standard protective measures [7]. The study compared intubation of mannequins using a standard laryngoscope, a video laryngoscope, or cricothyrotomy.…”
Section: Setup and Our Experience With The Rega Piumentioning
confidence: 99%
“…Interestingly, we found only one study performed with anaesthesiologists as subjects. 13 Two studies have confirmed that even staff with prior experience took significantly longer to achieve successful airway management whilst wearing PPE compared with not wearing it. 17,18 Clinical studies with risk of contamination with highly infectious pathogens would be unethical, so simulation studies should be encouraged for two main reasons.…”
mentioning
confidence: 99%
“…Five studies investigated only intubation, 11,12,14e16 one evaluated only supraglottic airway device placement, 10 and one included both intubation, supraglottic airway device placement and cricothyroidotomy. 13 The participants in these studies ranged from paramedic students (with no airway management experience 1011 ) to anaesthesiologists 13 ; the number of participants ranged from 1616 to 66. 11 The type of PPE worn also varied considerably.…”
mentioning
confidence: 99%
See 2 more Smart Citations